Evaluation of the anti-rheumatic properties of thymol using carbon dots as nanocarriers on FCA induced arthritic rats - Murugesan, Selvakumar; Srinivasan, Venkatesan; Lakshmanan, Dinesh Kumar; Venkateswaran, Meenakshi R; Jayabal, Sasidharan; Muthukumar Nadar, M. S. A; Kathiravan, Arunkumar; Asha Jhonsi, Mariadoss; Thilagar, Sivasudha; Periyasamy, Sureshkumar (Food & function, 2021)
Rheumatoid Arthritis (RA) is an autoimmune disease that commences as inflammation and progressively destroys the articular joint. In this study, we assess the anti-rheumatic potential of the monoterpenoid class of thymol conjugated with Carbon Dots (CDs). Waste biomass in the form of dried rose petals was chosen as a precursor for the synthesis of CDs via a one-step hydrothermal bottom-up methodology. The prepared CDs exhibited absorption in the near-visible region, and unique excitation-dependent emission behaviour was confirmed from UV-Visible and fluorescence measurements. The surface morphology of CDs was confirmed by SEM and HR-TEM analysis to be quasi-spherical particles with an average size of ∼5-6 nm. The presence of various functional moieties (hydroxyl, carbonyl, and amino) was confirmed via FT-IR measurement. The graphitization of CDs was confirmed by the D and G bands for sp 2 and sp 3 hybridization, respectively, through Raman analysis. Esterification methodology was adopted to prepare the CDs-thymol conjugate and confirmed via FT-IR analysis. CDs play the role of a nanocarrier for thymol, an anti-arthritic agent. The bioactive compound of thymol showed potent anti-arthritic activity against RA targets through in silico docking studies. Further, the in vivo studies revealed that CDs-thymol conjugates (10 mg per kg body weight) showed a significant reduction in rat paw volume along with reduced levels of RF and CRP (2.23 ± 0.42 IU ml −1 and 16.96 ± 0.22 mg ml −1 ) when compared to the disease control rats. X-ray radiography and ultrasonic imaging revealed less bone destruction, joint derangement, and swelling in arthritis-induced Wistar rats. They could also potentially improve the Hb (14.14 ± 0.19), RBC (6.01 ± 0.11), PCV (6.01 ± 0.11) levels and elevate the status of antioxidant enzymes (GPx, SOD, MDA), and the activity was comparable to the standard drug, ibuprofen (10 mg kg −1 ), suggesting that the CDs-thymol conjugate at 10 mg kg −1 could act as a strong anti-arthritic agent. This work is evidence for the utilization of waste biomass as a value-added product such as a nanocarrier for biomedical applications. The anti-rheumatic properties of thymol conjugated carbon dots.